FREQUENCY OF KENNEDY’S CLASSIFICATION AMONG PARTIALLY EDENTULOUS PATIENTS PRESENTING AT A TERITIARY CARE HOSPITAL IN ISLAMABAD - Rida Anjum; Ahmad Shoaib; Sunia Gul; Salman Ahmad (Pakistan Oral & Dental Journal, 2021)
The objective of the study was to figure out the frequency of Kennedy’s classification among partially edentulous patients presenting to the Department of Prosthodontics at Islamic International Dental Hospital, Islamabad. The study design was cross sectional and was conducted over a 6 month period (September 2018-February 2019) on patients reporting to the Prosthodontics Department at Islamic International Dental Hospital, Islamabad. 151 partially edentulous patients were selected using convenience sampling. Patterns of partial edentulousness were recorded according to Kennedy’s classification and were registered on to a well-structured proforma. The mandibular data demonstrated a higher recurrence of partial edentulism i.e. 53.5% as compared to maxillary arch which was 46.5% .The overall greatest prevalence of Kennedy’s classification was class III. The overall most dominant partial tooth loss trend was found to be Kennedy Class III. Both maxilla (65.7%) and mandible (53.5%) individually showed higher prevalence of Kennedy class III pattern. Moreover the most prevalent combination of Kennedy class was of class III in maxilla alongside Class III in mandible. Women showed higher percentage of partial edentulism than men. According to age, the most prevalent Kennedy class i.e. Class III was found more common in the patients aged 25-50 years. Hence, the present study inferred that amongst the occupants of Islamabad, Kennedy’s Class III was the most frequently occurring partially edentulous state irrespective of gender and age.